2019
DOI: 10.1097/md.0000000000014940
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of 13 antimicrobial dressings and different securement devices in reducing catheter-related bloodstream infections

Abstract: Purpose: The purpose of our study is to carry out a Bayesian network meta-analysis comparing the efficacy of different antimicrobial dressings for prevention of catheter-related blood infections (CRBSI) and rank these antimicrobial dressings for practical consideration. Methods: We searched the PubMed, Cochrane library, Embase, earlier relevant meta-analysis and reference lists of included studies for randomized controlled trials (RCTs) that compared dressings for preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
0
9
0
2
Order By: Relevance
“…Randomized trials and meta-analyses have shown no difference in risk of CRIs between single- or multiple-lumen CVC, and therefore, a preferred use of single-lumen catheters is not supported [ 151 153 ]. The use of sutureless devices was found to reduce the risk of CRI in a randomized study and in two meta-analyses accounting for multiple treatments [ 141 , 142 , 154 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Randomized trials and meta-analyses have shown no difference in risk of CRIs between single- or multiple-lumen CVC, and therefore, a preferred use of single-lumen catheters is not supported [ 151 153 ]. The use of sutureless devices was found to reduce the risk of CRI in a randomized study and in two meta-analyses accounting for multiple treatments [ 141 , 142 , 154 ].…”
Section: Resultsmentioning
confidence: 99%
“…CVC gauze dressings should be replaced every 2 days, transparent dressings once weekly, unless there are signs of local contamination, inflammation, or detachment [1,25,27,140]. Whether the use of gauze or transparent dressings is preferable in terms of lower CRI rates was addressed in two recent meta-analyses [141,142]. Dang and colleagues reported that transparent dressings were associated with a lower risk of CRBSI [142].…”
Section: Cvc Site Dressing and Anti-infective Capsmentioning
confidence: 99%
See 1 more Smart Citation
“…To rank the treatments for each outcome, we used the surface under the cumulative ranking curve (SUCRA) and the mean ranks, SUCRA would be 100% when a treatment is certain to be the best and 0 when a treatment is certain to be the worst, and higher posterior probabilities in each simulation indicates the higher chance of being the best treatment regimen. [29,30]…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of a positive blood culture, blind adjudication of the diagnosis of CAI is important to prevent differential detection bias. Of note, only six of 35 RCTs comparing antimicrobial dressings had a blind outcome assessment [96].…”
Section: Catheter-associated Infectionmentioning
confidence: 99%